Analisis Yuridis Pertimbangan Hakim Terhadap Perkara Wanprestasi : (Studi Kasus 219/Pdt.GS/2023/PN Pti) - Syahrul Rizqi Ramadhan; Dania Maulinda; Ulfa Kurnia Sari; Suwandoko Suwandoko (Jurnal Hukum dan Sosial Politik, 2024)
Issues regarding non-performance of an agreement can be resolved in two ways, namely outside court and through court. The Pati Court is one of the courts that handles many default resolutions, in terms of settlement through the courts. The judge's consideration is an important component in determining the fate of both parties, namely the plaintiff and defendant, who in terms of the agreement are creditor and debtor. We can see the judge's considerations in the case of default in case number 219/Pdt.GS/2023/PN.Pti. The aim of this research is to find out how considerations are taken to decide a case of tort and how the proof of the elements of tort is fulfilled. The research method used is a normative juridical method with a statutory approach, norms contained in regulations regarding agreements and a case approach. The results of the research show that, according to article 1320 of the Civil Code, the legal conditions for an agreement are agreement, competence, certain objects or things, and cause or lawful reasons, and it is stated in article 1238 of the Civil Code that a person is considered to be in default when he is negligent and does not carry out his obligations until after the time limit specified in the agreement he has agreed to. The judge's considerations in deciding case number 219/Pdt.GS/2023/PN Pti. is appropriate because based on the written evidence attached by the Plaintiff at the trial, then according to the evidence attached the Defendant is declared guilty or in default.